The Effectiveness of Implementing Learning Style Differentiation on Science Learning Interests and Outcomes in Elementary Schools - Eliya Kusuma Pratiwi; Dewi Nilam Tyas (Postgraduate, University of Mataram, 2025)
From the results of interviews and observations in Class IV of Al-Akhyar Islamic Elementary Schoollow interest and learning outcomes were found. This was caused by teachers who only used the lecture method when explaining without analyzing the characteristics of their students. Therefore, this study was conducted with the aim ofexamines the influence of differentiation learning styles on interest and learning outcomes of elementary school science students. This type of research is a quasi-experiment. The population of the study was all fourth-grade students of SDIT Al-Akhyar Kudus, with a sample of class IV A as an experimental class with the (PBL) Problem Based Learning model with learning style differentiation and class IV B as a control class with the (PBL) Problem Based Learning model without learning style differentiation. Data collection used a learning interest questionnaire and learning outcome test. Data analysis was carried out descriptively (percentage of learning interest) and parametric inferential (normality test, homogeneity, Independent Sample T-test, and Ngain for learning outcomes). The results showed that students' learning interest increased significantly after being given differentiation learning, from 65.5% to 85.2%. The results of the N-gain test for the experimental class were 0.63 with a fairly effective category from the control class 0.52 with a less effective category. In conclusion, differentiated learning is effective in improving students' interest and learning outcomes.